A gold(i)-catalyzed substituent-controlled cycloisomerization of propargyl vinyl ethers to multi-substituted furofuran and furopyran derivatives. Issue 37 (16th March 2016) - Liu, Yongxiang; Jin, Shengfei; Wang, Yanshi; Cui, Shanshan; Peng, Xiaoshi; Niu, Yuanyuan; Du, Chuan; Cheng, Maosheng
Abstract : A gold(i )-catalyzed substituent-controlled strategy for the stereoselective synthesis of bicyclic furan and pyran derivatives has been developed. Abstract : A gold(i )-catalyzed substituent-controlled strategy for the stereoselective synthesis of bicyclic furan and pyran derivatives has been developed. The mechanisms of the reactions have been studied thoroughly by deuterium labelling experiments. The applications of the methodologies were demonstrated by evaluating the preliminary anti-fungal activity of the synthetic compounds.